A Comparative Study of Grade 2 Students’ Motivation for Learning English as a Foreign Language Under Game-Based Learning Method and Teacher-Centered Learning Method at a Demonstration School, Bangkok, Thailand - Meethongkhow, Teerada; Adedin Forhad, Ziaul (Scholar: Human Sciences, 2021)
The purpose of this study was to compare students’ motivation for learning English as a foreign language under game-based learning method and teacher-centered learning method of Grade 2 students at a Demonstration school, Bangkok, Thailand. This research study involved five objectives which included; Grade 2 students’ motivation level for learning English as a foreign language under game-based learning method and teacher-centered learning method in pre-test and post-test. The significant difference in Grade 2 students’ motivation level for learning English as a foreign language under teacher-centered and game-based learning method between pre-test and post-test individually and finally comparing the significant difference in Grade 2 students’ motivation level for learning English as a foreign language under game-based learning method and teacher-centered learning method between pre-test and post-test. The data were collected by using the pre-test and post-test. The scores were analyzed by means, paired samples t-test and independent samples t-test. The finding of the study showed that, students motivation level in game-based learning method was higher than the students in the teacher–centered learning method in Grade 2 of the Demonstration school, Bangkok, Thailand. The study demonstrated the effectiveness of learning English as a foreign language under game-based learning method. Recommendations have been suggested for the school, teachers and the future researchers.